2020
DOI: 10.21203/rs.2.20489/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of STIP1 and GLCCI1 polymorphisms on the risk of childhood asthma and inhaled corticosteroid response in Chinese asthmatic children

Abstract: Background: Asthma is a common chronic lung disease in children. We aimed to determine the associations between stress-induced phosphoprotein 1 (STIP1) and glucocorticoid-induced transcript 1 (GLCCI1) polymorphisms and susceptibility of childhood asthma and inhaled corticosteroid (ICS) response in children. Methods: A total of 263 Chinese Han asthmatic children were recruited from the Xiangya Hospital, Central South University. Pulmonary function tests were performed before the treatment and 3 months after th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…asthma, autophagy, glucocorticoid-induced transcript 1 gene, WD repeat domain 45B hyper-responsiveness. 7 In our previous study, we found that expression of GLCCI1 is associated with the changes of forced expiratory volume in 1 second in asthmatic patients accepted with fluticasone propionate treatment. 8 Moreover, in our previous study, we also demonstrated that knockout GLCCI1 in asthmatic mice could attenuate the therapeutic outcome of hydroprednisone.…”
Section: Introductionmentioning
confidence: 85%
“…asthma, autophagy, glucocorticoid-induced transcript 1 gene, WD repeat domain 45B hyper-responsiveness. 7 In our previous study, we found that expression of GLCCI1 is associated with the changes of forced expiratory volume in 1 second in asthmatic patients accepted with fluticasone propionate treatment. 8 Moreover, in our previous study, we also demonstrated that knockout GLCCI1 in asthmatic mice could attenuate the therapeutic outcome of hydroprednisone.…”
Section: Introductionmentioning
confidence: 85%